2001
DOI: 10.1002/1521-3765(20010202)7:3<585::aid-chem585>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Facile Solid-Phase Synthesis of an Antifreeze Glycoprotein

Abstract: The antifreeze glycoproteins (AFGPs) 1 are composed of a repeating tripeptide unit (Ala-Thr-Ala) in which the threonine residue is glycosylated with the disaccharide beta-D-Gal-(1-->3)-alpha-D-GalNAc. A new procedure for synthesizing AFGPs using Fmoc-(Ac4-beta-D-Gal-(1-->3)-benzylidene- alpha-D-GalNAc)Thr-OH (10) as a building block has been developed. Total synthesis of the AFGPs (n = 4, 8) in overall yields of 61% and 33 %, respectively, has demonstrated the usefulness of the method. The synthetic AFGPs 1 (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…An alternate route to high molecular mass AFGPs using solid-phase peptide synthesis has recently been reported (Fig. 6B) using Fmoc-chemistry and standard protecting groups to produce AFGPs where n ¼ 4 and 8 [77]. Related solid-phase synthesis [78,79] of AFGPs containing single sugars should allow access analogues for structure-activity studies.…”
Section: Synthesis Of Antifreeze Glycoproteinsmentioning
confidence: 99%
“…An alternate route to high molecular mass AFGPs using solid-phase peptide synthesis has recently been reported (Fig. 6B) using Fmoc-chemistry and standard protecting groups to produce AFGPs where n ¼ 4 and 8 [77]. Related solid-phase synthesis [78,79] of AFGPs containing single sugars should allow access analogues for structure-activity studies.…”
Section: Synthesis Of Antifreeze Glycoproteinsmentioning
confidence: 99%
“…The synthesis of the glycosylated building block relied on the direct azidochlorination of 3-(galactosyl)-galactal. The suggested method of synthesizing Fmoc-Thr with the disaccharide α- d -galactosyl-(1 → 3)-β- N -acetyl- d -galactosamine attached to the side chain required fewer synthetic steps compared with the method reported by Tseng et al ( 2001 ), and was a selective, reliable, and scalable method of obtaining the building block.
Fig.
…”
Section: Recent Approaches In the Synthesis Of Afgpsmentioning
confidence: 99%
“…However, their analogues were extremely simplified forms of the natural AFGPs, lacking the terminal galactose and the N -acetyl groups. Tseng et al ( 2001 ) reported the solid-phase synthesis of natural AFGPs in 2001. Initially, the glycosylated amino acid was prepared in 60% yield.…”
Section: Synthesis Of Native Afgps and Afgp Analoguesmentioning
confidence: 99%
“…Several alternative approaches were developed to overcome the dispersity in sequence and length of the AFGP analogues prepared by solution phase polymerization. To this end, Wilkingson [87] and Tseng [87,88] first prepared oligomers with a well-defined sequence and length by SPPS employing Fmoc-protected amino acids. In a following step, these were coupled using benzotriazole-1-yloxytris (pyrrolidino)phosphonium (PyBOP) hexafluorophosphate [87,88].…”
Section: Production Of Af(g)ps and Synthetic Analogues: Design Andmentioning
confidence: 99%